The Role of Spirituality in Health: The Importance of a Holistic Approach to Patients in Medical Practice - Munawwaroh, Siti Madinatul (UIN Sunan Gunung Djati Bandung, 2025)
In Indonesia, religiosity and spirituality have yet to become integral components of medical practice, often remaining separate from conventional approaches such as pharmacological treatments and psychotherapy. Despite most Indonesian physicians adhering to a particular religion, spirituality-based care is rarely applied in clinical settings. Interestingly, surveys from hospitals in the United States reveal that patients desire spiritual dimensions in their healthcare. This study explores the intricate connection between spirituality and health, emphasizing the importance of addressing patients' spiritual needs in the healing process. Employing library research and qualitative descriptive analysis, the findings highlight how spirituality acts as a powerful internal source of strength, fostering meaning, optimism, and resilience in the face of illness. The study reveals that individuals with strong spiritual awareness tend to have more positive attitudes, constructive stress responses, stronger immune systems, and faster recovery times. Historically intertwined with medicine, spirituality has been marginalized in Western practices but remains central in Eastern traditions. The results advocate for healthcare professionals to adopt a holistic approach that integrates biological, psychological, social, cultural, and spiritual dimensions, ultimately enhancing patient well-being and advancing medical practice.